Redevelopment of the Arctic Area of Russia as an Objective of Systems Research and Special-Purpose Program Management Methodological Issues - Leksin, Vladimir Nikolayevich; Porfiryev, Boris Nikolayevich (Economy of Regions, 2015)
The paper substantiates the methodological foundations of implementation of the rules and regulations of the development of the Arctic region of Russia, which relies on the hypothesis interpreting such development as the biggest integrated megaproject in the history of Russia. The substantiation involves both the project-oriented approach to identify the subject-matter of the research and the systems approach to assess the key opportunities of providing the integrative structure of the megaproject in the conditions of drastic differences between the areal components of the Arctic region, and to study the internal and external factors’ impact on the character, drivers and pace of the region redevelopment. The set of consistent methodological positions concerning their policy implementation by responsible governmental agencies in the foreseeable future of the Arctic is developed. The most important position involves the identification of the objective of the public administration of the Arctic region development as a systemically organized entity of multiple coordinated actions of the federal, regional and municipal authorities, corporations and civil society institutions integrated by the unique policy target and economic, social and infrastructure links. Implementation of the public administration requires the principles of systems approach, the reasonable trade-off between centralization, decentralization and continuity of governance focused exclusively on the Arctic issues. At the same time, the integration of the projects of the region’s areal components development to insure the common targets of the Arctics megaproject accompanied by the reconsideration of the earlier developed programs turns into a genuinely new methodological issue. In the article, recommendations to provide such integration are introduced.